2017
DOI: 10.1107/s2414314617000323
|View full text |Cite
|
Sign up to set email alerts
|

3-Phenylisoxazolin-5-one: a redetermination

Abstract: The structure of the title molecule, C9H7NO2, has been redetermined to improved precision and the H atoms located [Cannaset al.(1969).Acta Cryst.B25, 1050]. The five-membered ring is almost planar (r.m.s. deviation = 0.006 Å) and subtends a dihedral angle of 2.45 (6)° with the benzene ring. In the crystal, molecules form ribbons running parallel to thea-axis direction through a combination of C—H...N and C—H...O hydrogen bonds. `Stair-step' offset π–π stacking interactions are also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to their results, the compound behaved as an efficient inhibitor with IE of 97% at 10 −3 M. The IEs of two synthesized 1,5‐benzodiazepine derivatives against carbon steel corrosion in 1 M hydrochloric acid were studied. These compounds showed IE of 89% and 94% at 10 −3 M. [ 20 ] Essaghouani et al [ 21 ] studied the corrosion inhibition properties of 1‐ethyl‐4‐phenyl‐2,3‐dihydro‐1 H ‐1,5‐benzodiazepin‐2‐one for mild steel in 1 M hydrochloric acid. According to their results, the compound showed IE of 92% at 10 −3 M.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to their results, the compound behaved as an efficient inhibitor with IE of 97% at 10 −3 M. The IEs of two synthesized 1,5‐benzodiazepine derivatives against carbon steel corrosion in 1 M hydrochloric acid were studied. These compounds showed IE of 89% and 94% at 10 −3 M. [ 20 ] Essaghouani et al [ 21 ] studied the corrosion inhibition properties of 1‐ethyl‐4‐phenyl‐2,3‐dihydro‐1 H ‐1,5‐benzodiazepin‐2‐one for mild steel in 1 M hydrochloric acid. According to their results, the compound showed IE of 92% at 10 −3 M.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several benzodiazepine derivatives were investigated as corrosion inhibitors in an acidic medium. [18][19][20][21] Sikine et al [18] investigated 1H-benzo[b] [1,4]diazepine-2,4(3H,5H)-dione as a corrosion inhibitor for mild steel in 1 M hydrochloric acid. The results of the study showed good corrosion inhibition performance of the studied compound with inhibition efficiency (IE) of 92% at a concentration of 10 −3 M. El Aoufir et al [19] evaluated 1,5-benzodiazepine derivative, namely, 4Z-(2-oxopropyl)-1,3-bis(prop-2-yn-1-yl)-2,3,4,5-tetrahydro-1,5-benzodiazepin-2-one, as a corrosion inhibitor for carbon steel in 1 M hydrochloric acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation